Preparation and characterization of Zr and Sn doped TiO2 nanocomposite and photocatalytic activity in degradation of tetracycline. Issue 23 (14th May 2016) - Pouretedal, H.R.; Afshari, B.
Abstract: The photocatalysts of Ti0.9 Zr0.03 Sn0.07 O2, Ti0.9 Zr0.05 Sn0.05 O2, and Ti0.9 Zr0.07 Sn0.03 O2 nanocomposite were prepared using the sol–gel method. The structure of anatase–rutile for prepared photocatalysts was confirmed using X-ray diffraction patterns. The transmission electron microscope image indicated that the size of nanoparticles was in range of 30–80 nm. The elemental analysis of Ti0.9 Zr0.05 Sn0.05 O2 nanocomposite was confirmed by energy dispersive X-ray analysis. The UV–vis absorbance spectra of nanocomposites showed a red-shift of band-gap energies of semiconductors vs. TiO2 pure nanoparticles. The application of prepared nanophotocatalysts was studied in tetracycline photodegradation in aqueous samples. The complete degradation of pollutant in a photodegradation reaction with rate constant of 27.0 × 10 −3 min −1 was obtained at optimized conditions of 0.8 g/L of Ti0.9 Zr0.05 Sn0.05 O2, pH 3, 20.0 mg/L of tetracycline and during time 180 min. The photocatalytic activity of nanoparticles was seen as Ti0.9 Zr0.05 Sn0.05 O2 > Ti0.9 Zr0.07 Sn0.03 O2 > Ti0.9 Zr0.03 Sn0.07 O2 > TiO2 that is related to the band-gap energies as 2.95 < 2.99 < 3.22 < 3.28 eV, respectively. The reusability of Ti0.9 Zr0.05 Sn0.05 O2 photocatalyst was tested in four cycles of photodegradation process. The resistance against of photocorrosion is due to reproducibility of photocatalytic activity.